Biomarkers unbound (Nature biotechnology, 2012)
Controversies surrounding government walk-in rights or patent eligibility that grabbed headlines in recent weeks presage broader changes in biomarker patenting In recent weeks, biotech patenting has been shaken by two high-profile legal decisions. The good news is that the sheer scale and variety of biomedical data ushered in by evidence-based healthcare will create a myriad of exciting opportunities for biotech inventors and/or patents.